The Influence of Entrepreneurial Competencies, Entrepreneurial Orientation, Entrepreneurial Self-Efficacy, Entrepreneurial Network, and Government Business Support on MSME Performance: The Moderating Role of External Environment - Hariyadi Efendy; Elok Savitri Pusparini (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of entrepreneurial competencies, entrepreneurial orientation, entrepreneurial self-efficacy, entrepreneurial network, and government business support on the performance of Micro, Small, and Medium Enterprises (MSMEs), considering the role of the external environment as a moderating variable. A quantitative approach was employed by distributing questionnaires to MSME actors across various industrial sectors. Data analysis was conducted using multiple regression methods and moderation interaction tests to examine the direct and indirect influences among variables. The results show that all independent variables have positive and significant effects on MSME performance. Additionally, the external environment significantly moderates the relationships between entrepreneurial factors and MSME performance, either strengthening or weakening these effects depending on the external environment dynamics faced. These findings provide important implications for MSME actors, policymakers, and business support institutions in designing strategies that empower and strengthen MSMEs based on their internal potential and external support.